Diagnosis and management of superficial arteriovenous malformations: French healthcare network’s recommendations - Olivia Boccara; Didier Salvan; Claude Laurian; Caroline Degrugillier-Chopinet; Nathalie Degardin; Jean-Guillaume Dillinger; Julie Malloizel-Delaunay; Stéphane Mouton; Stéphane Munck; Annabel Maruani; Annouk Bisdorff-Bresson (Orphanet Journal of Rare Diseases)
Abstract Superficial arteriovenous malformations are rare fast-flow lesions. They consist of arteriovenous shunts, without cellular hyperplasia or proliferation, which develop in the surrounding tissues (cutaneous, subcutaneous, muscular, bone). Although benign, they are among the most severe of superficial malformations. Their evolution can be life-threatening in exceptional cases. With the aim of optimizing diagnosis and management worldwide, this  protocol offers a state of the art for the diagnosis and management of these diseases. To this end, the French healthcare network specialized in these diseases have drawn on literature data and experience. Developed from the French National Diagnosis and Care Protocol, it presents the patient journeys for initial and differential diagnoses, and personalized therapeutic strategies. This requires a multidisciplinary team, with specialized professionals in handling genetic, treatment and psychosocial issues.